The Alternative Way to Drive the Automobile Air-Conditioning, Improve Performance, and Mitigate the High Temperature: A Literature Overview - Setiyo, Muji; Soeparman, Sudjito; Wahyudi, Slamet; Hamidi, Nurkholis (Periodica Polytechnica Transportation Engineering, 2018)
Over fuel consumption and increasing in CO2 emissions are problems as compensation from the imposition of automobile A/C systems. Another problem is the extreme temperature when the car is parked under sunlight so that the thermal load becomes very large when A/C is turned on. Therefore, this article presents various methods to overcome the problem. Methods to reduce fuel consumption and to reduce CO2 emissions are done by application of VCC and the absorption system. Potential of turbo A/C system and combining vapor compression and LPG fuel system has also been studied. Potential of turbo A/C system and combining vapor compression and LPG fuel system has also been studied. Related to the mitigating of high temperature inside the car cabin when parked under sunlight, the addition of a ventilator and portable car cooling system is a promising option.